Analysis of Factors Associated with Adherence to Taking Medication in Pediatric Patients with Pulmonary Tuberculosis in Mesuji Regency, Lampung, Indonesia - Ferianis Setiawati; Anis Prima Dewi; Mardin (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2023)
Background: One disease that is still a health problem in the world, including Indonesia, is tuberculosis (TB) which is caused by germs Mycobacterium tuberculosis. The success of TB treatment requires patient compliance in taking antituberculosis drugs (OAT), family support such as supervision, and motivating TB sufferers are factors that play a role in patient compliance. This study aims to determine the factors associated with medication adherence in pediatric patients with pulmonary tuberculosis in Mesuji Regency, Lampung, Indonesia. Methods: This study was an observational study with a cross-sectional approach, where as many as 52 respondents were included in this study. Data collection through interviews using a structured questionnaire. The subject of the study consisted of tuberculosis patients who were reported to have attended treatment for at least two months in Mesuji Regency. Data analysis was carried out using SPSS using univariate and bivariate methods. Results: The results showed that 76.9% of respondents adhered to the treatment of pulmonary tuberculosis. Patient medication adherence to tuberculosis was influenced by the presence of drug side effects (p-value = 0.007) and the supervisor's support for taking medication (p-value = 0.021). Conclusion: Compliance with taking medication in tuberculosis patients is influenced by the presence of medication supervisors and the uncomfortable side effects of antituberculosis drugs.